Overcoming Challenges of Cranial Nerve Tractography: A Targeted Review. Issue 2 (12th July 2018) - Jacquesson, Timothée; Frindel, Carole; Kocevar, Gabriel; Berhouma, Moncef; Jouanneau, Emmanuel; Attyé, Arnaud; Cotton, Francois
Abstract: BACKGROUND: Diffusion imaging tractography caught the attention of the scientific community by describing the white matter architecture in vivo and noninvasively, but its application to small structures such as cranial nerves remains difficult. The few attempts to track cranial nerves presented highly variable acquisition and tracking settings. OBJECTIVE: To conduct and present a targeted review collecting all technical details and pointing out challenges and solutions in cranial nerve tractography. METHODS: A "targeted" review of the scientific literature was carried out using the MEDLINE database. We selected studies that reported how to perform the tractography of cranial nerves, and extracted the following: clinical context; imaging acquisition settings; tractography parameters; regions of interest (ROIs) design; and filtering methods. RESULTS: Twenty-one published articles were included. These studied the optic nerves in suprasellar tumors, the trigeminal nerve in neurovascular conflicts, the facial nerve position around vestibular schwannomas, or all cranial nerves. Over time, the number of MRI diffusion gradient directions increased from 6 to 101. Nine tracking software packages were used which offered various types of tridimensional display. Tracking parameters were disparately detailed except for fractional anisotropy, which ranged from 0.06 to 0.5, and curvature angle, which was set between 20° and 90°. ROI design has evolved towards a multi-ROI strategy. Furthermore, new algorithms are being developed to avoid spurious tracts and improve angular resolution. CONCLUSION: This review highlights the variability in the settings used for cranial nerve tractography. It points out challenges that originate both from cranial nerve anatomy and the tractography technology, and allows a better understanding of cranial nerve tractography.